The Research Data Centre of the German Federal Employment Agency: Data Supply and Demand between 2004 and 2009 - Jörg Heining (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The Research Data Centre (FDZ) of the German Federal Employment Agency (BA) in the Institute for Employment Research (IAB) was founded in 2004 and is intended mainly to facilitate access to BA and IAB micro data for non-commercial empirical research using standardised and transparent access rules. Five years after its foundation the FDZ is acknowledged as producer of innovative data products and has become an visible element of the research community. Furthermore, linkages to other data producers and the internationalization of data products and data access have been promoted by the FDZ.
Keywords: 330; Mikrodaten; Sozialforschung; Deutschland